The relationship of exposure to news media with attachment to the national ethos - Tamam, Ezhar; Yee, Wendy Mei Tien; Idris, Fazilah; Hamzah, Azimi; Mohamed, Zainal Abidin; Wong, Su Luan; Mohd Noor, Mansor (Universiti Putra Malaysia Press, 2005)
This study tested the assumption that national media played an important role in promoting a strong national ethos among Malaysians. As youth are heavy consumer of media and play important roles in further progressing the country economically and politically, it is very pertinent to examine the strength of the national ethos among the Malaysian youth of various ethnic groups, and the relationship between the exposure to the news media and strength of their national ethos. A total of 606 students from ten universities and colleges aged between 18 to 27 years were interviewed in a national survey using a self-administered questionnaire. Three dimensions of the national ethos emerged from the data and the students had positive perceptions toward selected characteristics of the country. However, there is a significant difference among the three ethnic groups in their degree of attachment to the three different dimensions of the national ethos. An overall exposure to the news media has a positive and significant relationship with the shared identity and future dimension, and shared history and values dimension of the national ethos.